Role of micronutrients and natural antioxidants in fighting against HIV; a quick mini-review - S. Saeidnia; M. Abdollahi (Iranian Society of Pharmacognosy, 2014)
Oxidative stress has been implicated in the progression of HIV to AIDS, since HIV usually replicates in a highly oxidized condition and CD4+ T lymphocytes can be activated via a cascade of internal oxidative pathways, which enhances the formation of proteins and enzymes. Thus, antioxidants should potentially be useful for the treatment and prevention of HIV infection as a new alternative strategy. Regarding the point that there are various approaches for treating the HIV-positive patients, antioxidant supplementation therapy alongside with other medications possesses many benefits. In fact, antioxidants and micronutrient supplements have been considered as a costly and short-term strategy to improve antioxidant deficiency. If diets come with sufficient education and scientific recommendations, they can provide a low-cost and long-term strategy to reduce oxidative stress, prevent micronutrient deficiency, and slow down HIV progression. This strategy may be applicable and beneficial particularly in countries around coast of Africa, where HIV is most common. Meantime these countries are rich of natural food resources. It seems that a healthy diet is the best way to insure proper nutrient intake, since it contains many nutrients not available in pills.